Review Studies of Scope and Measurement of Tourism Activities - Utama, I Gusti Bagus Rai; Marhaendra, Tjokorda Bagus Putra; Patni, Ni Luh Putu Suarmi Sri (Technium Social Sciences Journal, 2021)
This paper attempts to review the issue of the definition of tourism and methods of measuring tourism activities which have become important issues since 1960 and until now. Various components are involved, both individuals and organizations both locally, nationally, regionally, and internationally, such as the world tourism organization (WTO). However, in reality, there are still differences in the method of measuring travel and tourism activities, especially aspects of tourism demand and supply. So that the initial strategic step is to standardize the definition of tourism, tourists, travelers, and visitors. So that later it can be used widely by all parties both in local, national, and international contexts. The non-uniform use of the international definition of tourism using data from the WTO as a world organization has resulted in inaccurate data and information that cannot be widely used. In 1967 the standardization of the use of the terms visitor, tourist, and excursionist was recommended by UNWTO, the result of the meeting in Geneva which was a revision of the decision in 1963. Several standardizations were carried out by UNWTO including the use of models that have been adopted by countries in the world, namely; Tourism Statistics Account (TSA) is a method for harmoniously measuring tourism demand and supply. So that existing weaknesses can be eliminated and new standards by the development of the academic world and the practical world, which can be used in a destination.